The coronavirus (COVID‐19) fatality risk perception of US adult residents in March and April 2020. Issue 4 (10th June 2020) - Niepel, Christoph; Kranz, Dirk; Borgonovi, Francesca; Emslander, Valentin; Greiff, Samuel
Abstract : The study compares empirical results on the coronavirus SARS‐CoV‐2 (causing COVID‐19) fatality risk perception of US adult residents stratified for age, gender, and race in mid‐March 2020 ( N1 = 1, 182) and mid‐April 2020 ( N2 = 953). While the fatality risk perception has increased from March 2020 to April 2020, our findings suggest that many US adult residents severely underestimated their absolute and relative fatality risk (i.e., differentiated for subgroups defined by pre‐existing medical conditions and age) at both time points compared to current epidemiological figures. These results are worrying because risk perception, as our study indicates, relates to actual or intended health‐protective behaviour that can reduce SARS‐CoV‐2 transmission rates.